Relationship between personality and entrepreneurial inclination among university students - Mohd. Othman, Fazilah; Abdul Mutalib, Rozita; Ahmad, Zalinah; Ismail, Nur Syakiran Akmal (2007)
Each year the number of graduates escalates in juxtaposition with unemployment issues.Consequently, in this coming age they can neither depend entirely on the government's effort to provide sufficient job nor for the industries to create more job openings than there already exist.Graduates now have to be proactive in determining their career paths and explore other possibilities for a living.Malaysia is currently encouraging its people to engage in entrepreneurial activities as a field of work.Abundance of programs aids at various levels are injected to foster entrepreneurship.Despite the government's aspiration and support, graduates still appear hesitant to embark on this profession enthusiastically. Universiti Utara Malaysia (UUM) has established an Entrepreneurship Development Institute (EDI) in its effort to promote this field.Besides focusing on academic matters, students also have the opportunity to experience 'hands-on' activities in entrepreneurship programs such as, operating business on campus,attending workshops and courses on entrepreneurship as well as given on-going consultation.These programs are available throughout their academic tenure on campus.Nevertheless, the process of evoking students' interests in entrepreneurship is challenging.The fact that people have different personalities and interests this research initially.In this paper we explore the relationship between personality and entrepreneurial inclination among students at UUM. Upon analyses we found the five personality dimensions positively correlate with entrepreneurial inclination.To date, paradoxically the number of graduates proven actually venturing into entrepreneurship remains parochial. Further implications on the results are also discussed.